Brief Report: Human Perivascular Stem Cells and Nel‐Like Protein‐1 Synergistically Enhance Spinal Fusion in Osteoporotic Rats. (9th September 2015) - Lee, Soonchul; Zhang, Xinli; Shen, Jia; James, Aaron W.; Chung, Choon G.; Hardy, Reef; Li, Chenshuang; Girgius, Caroline; Zhang, Yulong; Stoker, David; Wang, Huiming; Wu, Benjamin M.; et al.
Abstract Autologous bone grafts (ABGs) are considered as the gold standard for spinal fusion. However, osteoporotic patients are poor candidates for ABGs due to limited osteogenic stem cell numbers and function of the bone microenvironment. There is a need for stem cell‐based spinal fusion of proven efficacy under either osteoporotic or nonosteoporotic conditions. The purpose of this study is to determine the efficacy of human perivascular stem cells (hPSCs), a population of mesenchymal stem cells isolated from adipose tissue, in the presence and absence of NELL‐1, an osteogenic protein, for spinal fusion in the osteoporosis. Osteogenic differentiation of hPSCs with and without NELL‐1 was tested in vitro. The results indicated that NELL‐1 significantly increased the osteogenic potential of hPSCs in both osteoporotic and nonosteoporotic donors. Next, spinal fusion was performed by implanting scaffolds with regular or high doses of hPSCs, with or without NELL‐1 in ovariectomized rats (n = 41). Regular doses of hPSCs or NELL‐1 achieved the fusion rates of only 20%–37.5% by manual palpation. These regular doses had previously been shown to be effective in nonosteoporotic rat spinal fusion. Remarkably, the high dose of hPSCs+NELL‐1 significantly improved the fusion rates among osteoporotic rats up to approximately 83.3%. Microcomputed tomography imaging and quantification further confirmed solid bony fusion with high dose hPSCs+NELL‐1. Finally, histologically, direct in situ involvement of hPSCs in ossification was shown using undecalcified samples. To conclude, hPSCs combined with NELL‐1 synergistically enhances spinal fusion in osteoporotic rats and has great potential as a novel therapeutic strategy for osteoporotic patients. Stem Cells2015;33:3158–3163